Avaliação Em Saúde: Alicerce Para a Prática 2021
DOI: 10.22533/at.ed.2812130113
|View full text |Cite
|
Sign up to set email alerts
|

A Felicidade Na Voz De Idosos Institucionalizados

Abstract: Direitos para esta edição cedidos à Atena Editora pelos autores. Open access publication by Atena Editora Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição-Não-Comercial-NãoDerivativos 4.0 Internacional (CC BY-NC-ND 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…In the category "care of the collection equipment and supplies", it was observed that "assess peristomal skin integrity" was the most common requisite. The least frequent requisites were "carefully remove adhesive parts of the collection equipment" (10; 12.0% [25,28,40,41,43,46,50,71,75,77]), "check for signs of leakage in the collection equipment" (9; 10.3% [20,25,27,33,43,47,60,74,79]), "adjust the opening of the collection equipment in the first weeks after surgery" (7; 8.0% [29,45,47,51,74,79,92]), "carefully place the collection equipment around the stoma" (6; 6.9 % [16,24,25,73,83,84]), "take extra supplies and collection equipment when away from home" (6; 6.9% [6,15,75,83,86,87]), "fix the collection equipment correctly from bottom to top on the peristomal skin" (6; 6.9% [11,27,33,41,83,84]), "identify and perform the ch...…”
Section: Resultsmentioning
confidence: 99%
“…In the category "care of the collection equipment and supplies", it was observed that "assess peristomal skin integrity" was the most common requisite. The least frequent requisites were "carefully remove adhesive parts of the collection equipment" (10; 12.0% [25,28,40,41,43,46,50,71,75,77]), "check for signs of leakage in the collection equipment" (9; 10.3% [20,25,27,33,43,47,60,74,79]), "adjust the opening of the collection equipment in the first weeks after surgery" (7; 8.0% [29,45,47,51,74,79,92]), "carefully place the collection equipment around the stoma" (6; 6.9 % [16,24,25,73,83,84]), "take extra supplies and collection equipment when away from home" (6; 6.9% [6,15,75,83,86,87]), "fix the collection equipment correctly from bottom to top on the peristomal skin" (6; 6.9% [11,27,33,41,83,84]), "identify and perform the ch...…”
Section: Resultsmentioning
confidence: 99%
“…No que tange a felicidade, trata-se de um fenômeno social, assim como institucionalizar uma pessoa idosa, pois a vivência de ambos é singular. Cada pessoa vivencia suas concepções e expectativas pessoais (KACZALLA, 2017).…”
Section: Discussionunclassified
“…Cada pessoa traz sobre si sua própria definição do que é felicidade, destacando ser uma emoção básica caracterizada por um estado emocional positivo, como sentimentos de prazer, gratidão, alcance de metas, ligados ao sucesso, sentimentos acarretados pelo longo da vida, solidariedade estando ligado também a aspectos da vida tais como amizades adquiridas, casamento, nascimento dos filhos, condições de saúde (KACZALLA, 2017).…”
Section: Discussionunclassified